2016
DOI: 10.1002/asna.201612334
|View full text |Cite
|
Sign up to set email alerts
|

The radio/X‐ray correlation in Swift J1753.5–0127

Abstract: Great effort has gone into trying to explain the two observed radio/X-ray correlation tracks seen in the low/hard state of black hole X-ray binaries in recent years. The original, "standard" correlation of the form L R ∝ L b X , where b = 0.7 ± 0.1, is paired with a separate, lower correlation track with a steeper slope of ∼ 1-1.4, at least at high luminosities. These outlier sources seem to show fainter radio emission than expected for a given X-ray luminosity, thus acquiring the term "radio-quiet". While mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…Instead of the 2.5 − 25 keV total Xray flux (F X ), using the 3 − 9 keV soft X-ray flux, we find a less steep exponent of b ∼ 1.05 ± 0.14. Our result is consistent with several other authors, who also have found a steeper exponent for this particular BHC with b ∼ 1.0 − 1.4 (Soleri et al 2010, Rushton et al 2016, Kolehmainen et al 2016. This BHC candidate is less luminous in radio which may be the reason behind getting a steeper index (Soleri et al 2010).…”
Section: Discussion and Concluding Remarkssupporting
confidence: 93%
See 1 more Smart Citation
“…Instead of the 2.5 − 25 keV total Xray flux (F X ), using the 3 − 9 keV soft X-ray flux, we find a less steep exponent of b ∼ 1.05 ± 0.14. Our result is consistent with several other authors, who also have found a steeper exponent for this particular BHC with b ∼ 1.0 − 1.4 (Soleri et al 2010, Rushton et al 2016, Kolehmainen et al 2016. This BHC candidate is less luminous in radio which may be the reason behind getting a steeper index (Soleri et al 2010).…”
Section: Discussion and Concluding Remarkssupporting
confidence: 93%
“…Several authors have found radio/X-ray correlation for this source. This does not fall on the traditional correlation track, rather, it shows power-law index to be steeper ∼ 1 − 1.4 (Soleri et al 2010, Rushton et al 2016, Kolehmainen et al 2016.…”
Section: Introductionmentioning
confidence: 93%